Bio-electro catalytic treatment of petroleum produced water: Influence of cathode potential upliftment. (November 2016) - Jain, Pratiksha; Srikanth, Sandipam; Kumar, Manoj; Sarma, Priyangshu M.; Singh, M.P.; Lal, Banwari
Graphical abstract: Highlights: Treatment of petroleum produced water was studied using BES. Upliftment cathode potential showed significant improvement in BES performance. Electrochemical analysis was done to study the change in redox reactions. Microbial dynamics showed dominant population from wastewater. Sulfate removal was low due to the non-possibility of strong reduction at anode. Abstract: Treatment of petroleum produced water (PPW) was studied using bioelectrochemical system (BES) under uplifted cathode potential. The treatment efficiency in terms of COD and hydrocarbon removal was observed at 91.25% and 76.60% respectively, along with the reduction in TDS during BES operation under 400 mV of cathode potential. There was also a reduction in concentration of sulfates, however, it was not significant at, since oxidative conditions are being maintained at anode. Improved oxidation of PPW at anode also resulted in good power output (−20.47 mA) and also depicted improved fuel cell behaviour. The electrochemical analysis in terms of cyclic/linear sweep voltammetry also showed well correlation with the observed treatment efficiencies. The microbial dynamics of the BES after loading real field wastewater showed the dominance of species that are reported to be effective for petroleum crude oil degradation.